KEKUATAN HUKUM PERJANJIAN PENGIKATAN JUAL BELI DALAM PROSES BALIK NAMA SERTIPIKAT (STUDI PUTUSAN NOMOR 635/PDT.G/2020/PN DPS) - Yapferonica, Yapferonica; Djaja, Benny; Sudirman, M. (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2025)
ABSTRACT; The Sale and Purchase Agreement Binding (Perjanjian Pengikatan Jual Beli/PPJB) is a preliminary agreement entered into between a prospective seller and a prospective buyer, containing mutual promises and stipulations that serve as a precondition for the execution of a definitive sale and purchase agreement. The main issues examined in this research are: (1) the legal force of the Sale and Purchase Agreement Binding, and (2) the legal protection afforded to the land buyer against the actions of the notary and the sixth defendant. This research adopts a normative legal research methodology with a descriptive approach. The data utilized in the study consist of secondary data, including primary and secondary legal materials, collected through literature review. The analysis is conducted using qualitative methods and conclusions are drawn deductively. The Sale and Purchase Agreement Binding dated February 1, 2013, possesses evidentiary value equivalent to that of an authentic deed and has been accepted as valid evidence in court proceedings. The buyer in this case is a bona fide purchaser who is entitled to legal protection through repressive legal measures. Kristian, as the seller, is deemed to have complied with the prevailing laws and regulations.